2012
DOI: 10.5923/j.materials.20110102.15
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Process Parameters on Microstructure and Mechanical Properties of Friction Stir Welded Al 5083 alloy Lap joint

Abstract: Recently the aircraft and military industries widely have been using aluminum alloys particularly because of their fine strength to weight ratio. However in compare with steels they represent welding difficulties and also lower ductility. In last years it has been observed that Friction Stir Welding (FSW) method represents better microstructure and mechanical properties than conventional methods in welding aluminum alloys. In this study experiments were performed to investigate the effects of FSW process param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…upward material flow) [20]. While its occurrence in the nugget zone has been associated with changes in material flow direction, from downward to upward, depending on tool geometry and welding conditions (hot or cold) [21].…”
Section: Effect Of Pin Geometry On the Macrostructure Of Fsw Jointmentioning
confidence: 99%
“…upward material flow) [20]. While its occurrence in the nugget zone has been associated with changes in material flow direction, from downward to upward, depending on tool geometry and welding conditions (hot or cold) [21].…”
Section: Effect Of Pin Geometry On the Macrostructure Of Fsw Jointmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that FSW is still viable with other types of joints namely step joint, flat 90°joint or T-lap joint [5,16]. Lap joints are widely used in assemblies of parts in aerospace and automotive industries.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, FSW has been the most suited for aluminum alloys lap joints [7]. H. Bisadi et al [8] studied the microstructure and mechanical properties in certain FSW process parameters (rotational and welding speed) for lap joint welding. The material used was 5083 aluminum alloy, 2.5 mm thick and the parameters applied were 600, 825, 1115, 1550 rpm rotational speeds and 32, 60 mm/min welding speeds,He found that A superior weld joint is obtained at lower rotational and welding speeds.…”
Section: Introductionmentioning
confidence: 99%